HUBUNGAN BEBERAPA FAKTOR PENYEBAB KEKERASAN DALAM RUMAH TANGGA (KDRT) PADA ISTRI PUS DI KELURAHAN TINJOMOYO KECAMATAN BANYUMANIK TAHUN 2016 - Septi Rani Dafeni; Atik Mawarni; Djoko Nugroho; Yudhy Dharmawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
According to WHO (2013), Domestic violence is any form of violence committed by husbands against wives that result in physical, psychological, sexual and economic harm, deprivation of liberty occurring within the household. Based on the annual report of the Integrated Service Center (PPT) SERUNI Semarang cases of violence against women increased from 2015 as many as 188 cases and 2016 as many as 199 cases, 81% experienced violence is domestic violence. Banyumanik sub-district is one of the sub-districts with the highest cases of domestic violence in 2016. Recorded 47% of cases of domestic violence in Banyumanik district occurred in Tinjomoyo. The incidence of domestic violence in Tinjomoyo village is influenced by many factors that cause in the community and surrounding environment. These factors may be Demographic factors, wife knowledge and gender inequalities. Type of research Explanatory Research with Cross Sectional Study study design. The population is the wife of EFA who as permanent resident in Banyumanik sub-district in 2016-2017 is 2,919 people. With sampling technique Simple Random Sampling samples obtained 100 wives. Data analysis used univariate analysis, bivariate analysis and Multivariate analysis. Based on the results of Univariat . The largest percentage is found in young married wife (14,0%), wife advanced education (72,0%), wife unemployment status (59,0%), low family income (53,0%) , Knowledge of wife less (88,0%), and gender inequality (55,0%) and incidence of domestic violence (51,0%) Result of bivariate analysis of chi square no relationship of wife marriage age (p value = 0,002), Family income (P value = 0.001) and gender inequality (p value = 0.001) with the incidence of domestic violence. Multivariate analysis results show the marriage age of first wife, family income and gender inequality influence with the incidence of domestic violence